Determination of trace elements in some fruits collected in Vietnam and Korea by Neutron Activation Analysis on Dalat and HANARO research reactors - Nguyen , Thi Sy; Ho , Manh Dung; Ho , Van Doanh; Tran , Quang Thien; Yong , Sam Chung (Nuclear Science and Technology, 2015)
The k0-based neutron activation analysis (k0-NAA) has been applied for determination of trace multi-element in 5 fruits: Orange, tomato, persimmon, pear and apple. The samples were collected in Vietnam and Korea, and dried-frozen in laboratory at a temperature of -650C, weighed approximately 50 mg or 100 mg each sample, and put in clean polyethylene bags for short and long time irradiations, respectively. The NIST-1547 (Peach Leaves) and IAEA-V-10 (Hay Powder) were used for the purpose of quality control. Both analytical and standard samples were irradiated in the 500 kW Dalat research reactor (Vietnam) and the 20 MW HANARO research reactor (Korea). Concentration of 16 elements: Al, As, Au, Br, Ca, Cl, Co, Eu, Fe, K, La, Mg, Mn, Na, Rb and Zn were determined. By comparison the concentrations of trace elements in the investigated Vietnam and Korea’s fruits, revealed that they are mostly similar between two places. However, the Ca concentration in orange from Vietnam was approximately 2.5 times higher than that one from Korea, whereas the Ca concentration in pear from Vietnam was approximately 21 times lower than that one from Korea. The Mn concentrations in all of fruits that collected in Vietnam were mostly higher than those collected in Korea, ranging between 1.4 to 2.2 times.